2019
DOI: 10.3390/su11195259
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Social Perception of Residential Solar Photovoltaic Systems in Saudi Arabia

Abstract: Saudi Arabia has taken major steps to shift from an oil-centered to more environmentally-focused economy. One approach made recently is to enable households to possess and generate electricity by using small-scale residential solar photovoltaic systems (RSPSs). However, the number of applications to install this technology in residences is significantly low. Social acceptance of solar energy is essential for a successful energy transition. Hence, the present study aims to examine factors that may potentially m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 34 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…A few scholars have conducted studies in developing countries as well to analyze the consumers' willingness to adopt solar PV. Alrashoud and Tokimatsu [37] examined considerations that may either empower or dissuade Saudi Arabian people from purchasing solar photovoltaic (PV) systems. The research found that education had the greatest positive effect, while the installation cost was the greatest barrier to adoption.…”
Section: Introductionmentioning
confidence: 99%
“…A few scholars have conducted studies in developing countries as well to analyze the consumers' willingness to adopt solar PV. Alrashoud and Tokimatsu [37] examined considerations that may either empower or dissuade Saudi Arabian people from purchasing solar photovoltaic (PV) systems. The research found that education had the greatest positive effect, while the installation cost was the greatest barrier to adoption.…”
Section: Introductionmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/2044-124X.htm these households due to availability and utility (Alrashoud and Tokimatsu, 2019;Qureshi et al, 2017).…”
mentioning
confidence: 99%
“…Faiers and Neame [13] used an innovation diffusion theory to investigate households' attitudes towards system attributes of the solar system and also identified barriers that prevent adopting technology in the UK. Similarly, research conducted in Saudi Arabia revealed factors that potentially motivate or impede the social perception of residential solar photovoltaic based on innovation diffusion theory [16]. Furthermore, Yadav et al [10] explored both perceptions and attitudes of rural women towards solar cookers in India.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Tsaur and Lin [15] in Taiwan also explored customers' attitudes towards building attached solar PV equipment using the technology acceptance model. Likewise, Alrashoud and Tokimatsu [16] in Saudi Arabia also studied factors influencing the social perception of residential solar PV systems. Moreover, Yadav et al [10] investigated both the perception and attitude of rural women towards solar in India.…”
Section: Introductionmentioning
confidence: 99%